PENGEMBANGAN EBOOK PERCAKAPAN BAHASA ARAB KELAS IV MI BERBASIS KONSTRUKTIVISME MENGGUNAKAN MODEL ADDIE - Ridha, Hafiz; Hamidah; Marsiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop Arabic ebook conversation teaching materials for sixth-grade Madrasah Ibtidaiyah students using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The teaching materials were developed based on the needs of MI level students who still face difficulties in mastering vocabulary and simple conversations. The teaching material product is an eBook entitled “Easy Arabic Conversation for Grade VI,” which contains 15 contextual muhadatsah themes. Validation was carried out by subject matter experts, media experts, and readability tests by teachers and students. The validation results showed that the teaching materials were in the “highly feasible” category in terms of relevance, accuracy, systematics, and learning significance. The responses from teachers and students indicated that the teaching materials were easy to understand, interesting, and helpful for cooperative learning. Thus, these constructivist-based conversation teaching materials are feasible for use as additional learning resources in Arabic language learning for sixth grade MI students.